2004
DOI: 10.1177/0095798404266063
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Sisters of Nia: A Cultural Program for African American Girls

Abstract: In this study, the authors evaluated the effectiveness of a cultural intervention for increasing cultural values and beliefs Fifty-nine African American girls in early adolescence participated in a 15-session cultural program or in an activity comparison group Measures of ethnic identity, gender roles, and relational aggression were administered at pretest and posttest There were significant increases in ethnic identity and a marginally significant increase in androgynous gender roles for girls in the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 26 publications
(30 reference statements)
1
65
0
Order By: Relevance
“…Yet psychologists and mental health professionals need not turn to journalistic guidelines to accomplish this task, as a minority of authors in our sample offered existing conceptual frames that would decrease cisgenderism in the literature. For example, a programme evaluation study of a cultural intervention with African American girls reported an increase in androgynous gender roles in the intervention group as a positive outcome and noted that the intervention decreased relational aggression (Belgrave et al, 2004). By avoiding the assumption that non-normative gender expression leads to developmental and social problems, Belgrave et al (2004) gained valuable data that suggests gender normativity and hypernormativity, rather than anormativity, as psychological risk factors for children.…”
Section: Discussionmentioning
confidence: 99%
“…Yet psychologists and mental health professionals need not turn to journalistic guidelines to accomplish this task, as a minority of authors in our sample offered existing conceptual frames that would decrease cisgenderism in the literature. For example, a programme evaluation study of a cultural intervention with African American girls reported an increase in androgynous gender roles in the intervention group as a positive outcome and noted that the intervention decreased relational aggression (Belgrave et al, 2004). By avoiding the assumption that non-normative gender expression leads to developmental and social problems, Belgrave et al (2004) gained valuable data that suggests gender normativity and hypernormativity, rather than anormativity, as psychological risk factors for children.…”
Section: Discussionmentioning
confidence: 99%
“…Those that did were grounded in relational-cultural theory, though the extent to which these discussions involved critical analyses of gender relations and power differentials in society was unclear. On the other hand, Sisters of Nia and the Cultural Enhancement Project specifically sought to foster gender androgyny amongst African American girls, based on research indicating that an androgynous gender identity predicts positive social and psychological development amongst adolescents, and African American girls in particular (Belgrave, Reed, Plybon, Butler, et al, 2004;Belgrave, Reed, Plybon, & Corneille, 2004;Evans, Whigham, & Wang, 1995;Townsend, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Attrition was 55.6 percent; no analysis of differential attrition Belgrave, Reed, Plybon, Butler, et al (2004) Quasi-experimental, matchedcomparison group design Equivalent at baseline on demographics, aggression, ethnic identity but not on gender androgyny Increases in ethnic identity and slight program effects on gender androgyny and relational aggression, controlling for baseline levels Attrition was 16.7 percent; no differential attrition on baseline and outcome measures Stack (2005) One pre-posttest, noncontrolled design; one quasi-experimental, nonequivalent comparison group design assessing the intensive mental health program Baseline group equivalence and attrition unknown Evaluation 1: 2.8 percent readmission and 19.7 percent re-offending rate one year after completion, for those who completed in 2003-2004; 2 to 3 percent of all graduates of Southern Oaks were serving an adult incarceration sentence as of 2005 Evaluation 2: fewer treatment girls were reincarcerated and had new charges after two years than controls; reduced self-harmful and assaultive behaviors and time spent in both security unit and state mental health institution placements (no statistical tests of significance) Burke et al (2003) Randomized, controlled design Equivalent on all measures at baseline Increased protective factors and reduced risk factors for completers, compared to non-completers; reductions in commitments to an institution after a new offense, compared to controls; program effects on school outcomes disappeared across follow-ups Risk score data unavailable for 11 percent of treatment girls and 19 percent of controls; no analysis of differential attrition RYSE program suffered from high attrition and nonequivalent groups (Le et al, 2003), and the WINGS program evaluation revealed mixed results (Burke et al, 2003). Here, effects on risk and protective factors were not evident in comparison to controls, as data were missing for control girls, and only one significant effect emerged for program "completers," relative to the control group members.…”
Section: Reduced Recidivism For African American Girlsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Making Choices: Social Problem Skills for Children" (Fraser, Day, Galinsky, Hodges, & Smokowski, 2004) and "Friend to Friend" (Leff et al, 2009) are two group interventions addressing Social Information Processing deficits, improving problem-solving skills, and increasing prosocial behaviors among middle age relationally aggressive children. Two more programs "Social Aggression Prevention Program" (Cappella & Weinstein, 2006) and "Sisters of Nia" (Belgrave et al, 2004) were designed to reduce adolescent girls' use of relational aggression, while increasing their empathy skills, social problemsolving abilities, and prosocial behaviors.…”
Section: Interventionsmentioning
confidence: 99%